Obstructive Uropathy: Double-J (DJ) Stenting or Percutaneous Nephrostomy (Medical Forum Monthly, 2024)
Objective: To compare the efficacy percutaneous nephrostomy and double-J stent in patients of ureteric obstruction.Study Design: Randomized controlled trialPlace and Duration of Study: This study was conducted at the Department of Urology, Bakhtawar Amin Medical and Dental Collage, Multan, Pakistan from July 2022 to December 2023.Methods: In Group A, double-J ureteral stent was inserted retrograde using aseptic cystoscopy technique under mild sedation or local anesthesia, which involved instilling 2% xylocaine gel into the urethra. In Group B, an ultrasound-guided percutaneous nephrostomy tube was inserted at the puncture site subcutaneously. Complications such as bleeding, hematuria, and septicemia in both groups were documented immediately post-operatively and during follow-up sessions on the 15th and 30th days using KUB sonography. Patients experiencing complications were managed according to hospital protocols.Results: In phase 1of outcome, both the groups had high success rates, but Group B 87.9% had a slightly higher success rate compared to Group A 76.6%. However, the difference is not statistically significant (p=0.176). In phase 2 of outcome, both the groups had very high success rates, Group B 98.9% again having a slightly higher success rate compared to Group A 97.4%.Conclusion: Percutaneous nephrostomy (PCN) demonstrated superior efficacy compared to double J stenting (DJS) in managing postoperative complications associated with the definitive treatment of ureteral obstruction, regardless of whether the obstruction was due to extrinsic or intrinsic malignancy.